2012
DOI: 10.1002/etc.1808
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the anthropogenic fraction of fatty alcohols in a terrestrial environment

Abstract: Fatty alcohols are naturally produced hydrocarbons present in all living organisms. They are also used in detergent and cosmetic formulations, may be sourced from either petroleum or biological materials, and are typically disposed of down the drain. This study was conducted on the Luray catchment, Virginia, USA, where sales data indicate that approximately 2 kg of fatty alcohols from detergent enter the wastewater every day. Reconstructing fatty alcohols in the influent on the basis of sales data indicated a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Modeled results from iSTREEM can identify the spatial distribution of worst‐case scenarios (highest exposure) on which monitoring efforts can be optimally focused. For example, a national site selection was conducted for monitoring surfactants in sediment using the iSTREEM model and related data sources to identify locations of highest potential exposure that were also within practical proximity to a sediment collection contractor (Sanderson et al ; Mudge et al ). Although the iSTREEM model currently does not directly incorporate a probabilistic component, the model can be used as a tool within a probabilistic assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Modeled results from iSTREEM can identify the spatial distribution of worst‐case scenarios (highest exposure) on which monitoring efforts can be optimally focused. For example, a national site selection was conducted for monitoring surfactants in sediment using the iSTREEM model and related data sources to identify locations of highest potential exposure that were also within practical proximity to a sediment collection contractor (Sanderson et al ; Mudge et al ). Although the iSTREEM model currently does not directly incorporate a probabilistic component, the model can be used as a tool within a probabilistic assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies by Mudge (2012) and Mudge et al (2008), Mudge et al (2010), and Mudge et al (2012) have shown that LCOHs from both fecal and detergent sources rapidly biodegrade in wastewater treatment facilities, as discussed below. In effluent, the remaining alcohols have a signature that is unlike influent, as a result of mixed-liquor in situ (bacterial) synthesis of alcohols.…”
Section: Surfactant Overviewmentioning
confidence: 98%
“…The alkyl chain length of LCOH (Table 1) was identified by the OECD HPV program to range from C 6 to C 22 (The Organisation for Economic Co-operation and Development [OECD], 2006); however, the typical range in detergents of interest is between C 9 to C 18 as verified in several monitoring programs for alcohol and alcohol-based surfactants (Mudge et al, 2008, 2010, 2012; Mudge, 2012). The alcohol group is usually located in the terminal position of the aliphatic chain, but not necessarily so, and are normally saturated (no double bonds).…”
Section: Surfactant Overviewmentioning
confidence: 99%
“…The δ 13 C for many crude oils is in the range of −23 to −28‰. This may be compared to −26 to −36‰ for terrestrial plant matter and −20 to −26‰ for unicellular algae (Mudge et al, 2012). Since these ranges overlap, this may not be definitive in separating out the two sources.…”
Section: Introductionmentioning
confidence: 99%